Membrane Trafficking in Osteoblasts and Osteoclasts: New Avenues for Understanding and Treating Skeletal Diseases - Zhao, Haibo (Traffic (Copenhagen, Denmark), 2012)
The endocytic and exocytic/secretory pathways are two major intracellular membrane trafficking routes that regulate numerous cellular functions in a variety of cell types. Osteoblasts and osteoclasts, two major bone cells responsible for bone remodeling and homeostasis, are no exceptions. During the past few years, emerging evidence has pinpointed a critical role for endocytic and secretory pathways in osteoblast and osteoclast differentiation and function. The endosomal membrane provides a platform to integrate bone tropic signals of hormones and growth factors in osteoblasts. In osteoclasts, endocytosis, followed by transcytosis, of degraded bone matrix promotes bone resorption. Secretory pathways, especially lysosome secretion, not only participate in bone matrix deposition by osteoblasts and degradation of mineralized bone matrix by osteoclasts; they may also be involved in the coupling of bone resorption and bone formation during bone remodeling. More importantly, mutations in genes encoding regulatory factors within the endocytic and secretory pathways have been identified as causes for bone diseases. Identification of the molecular mechanisms of these genes in bone cells may provide new therapeutic targets for skeletal disorders.